c y J.R.R. Tolkien ; edited by Christopher Tolkien ; with illustrations by Alan Lee. - Tolkien, J. R. R. (John Ronald Reuel), 1892-1973; Tolkien, Christopher; Lee, Alan (Boston : Houghton Mifflin Court, 2017)
Painstakingly restored from Tolkiens manuscripts and presented for the first time as a continuous and standalone story, the epic tale of Beren and Luthien will reunite fans of The Hobbit and The Lord of the Rings with Elves and Men, along with the rich landscape and creatures unique to Tolkiens Middle-earth.
Keywords: Middle Earth (Imaginary place) -- Fiction; Fantasy fiction